Increased Perception of Mosquito Problems During a Stormwater Restoration Project - Rosmarie Kelly (Georgia Southern University, 2015)
In 2008, a plan for improvement of the McDaniel Branch Watershed was prepared for the city of Atlanta, Department of Watershed Management. This included the construction of ponds in a kudzu-covered area at Bowen Circle. There is a perception that wetlands create mosquito problems. In point of fact, most of the vector and nuisance species in Atlanta are either container breeders or floodwater species, and do not breed in ponds. Because there is an average of 5 cases of West Nile virus (WNV) reported in Fulton County per year, most of these near Combined Sewer Overflow streams, county residents are aware of the connection between mosquitoes and WNV. As the McDaniel Branch Watershed Improvement Plan progressed, neighborhood residents became convinced that the changes being implemented in the area were increasing mosquito problems and increasing their risk of WNV infections. In Oct 2013, the Environmental Health Section of the Georgia Department of Public Health was contacted by the City of Atlanta Department of Watershed Management concerning control of mosquitoes in the ponds being created at the Bowen Circle site. It was determined that mosquito surveillance should be implemented in the area to determine if the changes to the watershed area were creating a mosquito problem. At the end of the 2014 mosquito surveillance season, it was established that there was little association between the watershed improvement project, the reported mosquito exposure, and measures of mosquito production within this neighborhood.